(untitled) (Journal of the College of Basic Education, 2022)
Poet critic Hussein Mardan presented documented data in his critical projectRelationship. between the text and the reader; It is a serious relationship; that requires that there be between him andThe text orbits in which their tools are w and the critic’s tools are the critical data available betweenhis hands; The text, in the opinion of the poet, cannot have an existence or a destiny without the reader.Because the reader is a producer of what he monitors, and then he reshapes the text according to what this endsThe relationship between them ’ is a relationship of transformation and interaction; competition and participation; And agreement and antagonism goThe reader and the text together, and all means of identification and self-openness are achieved for them.